Hamstring Contracture After ACL Reconstruction Is Associated With an Increased Risk of Cyclops Syndrome. Issue 1 (27th January 2017) - Guerra-Pinto, Francisco; Thaunat, Mathieu; Daggett, Matt; Kajetanek, Charles; Marques, Tiago; Guimaraes, Tales; Quelard, Bénédicte; Sonnery-Cottet, Bertrand
Background: Cyclops syndrome is characterized by loss of terminal knee extension due to proliferative fibrous nodule formation in the intercondylar notch. This complication occurs in the early postoperative period after anterior cruciate ligament reconstruction (ACLR). The pathogenesis of Cyclops syndrome is not well understood. Hypothesis: Persistent hamstring contracture after ACLR is associated with an increased risk of subsequent Cyclops syndrome. Study Design: Case-control study; Level of evidence, 3. Methods: The files of 45 patients who underwent arthroscopic debridement of a Cyclops lesion after ACLR were analyzed. Recorded data included demographic information and technical details of surgery. Preoperative magnetic resonance images were also analyzed, and patients with femoral bone bruising were identified. Passive and active range of motion were recorded in all patients preoperatively and at 3 and 6 weeks after surgery to address the Cyclops lesion. Passive extension deficit was evaluated in comparison with the contralateral limb and classified as secondary to hamstring contracture when contracture was observed and palpated in the prone position and when the extension deficit was reversed after exercises performed to fatigue the hamstrings. A control group was selected using a random numbers table among our entire ACLR cohort. Statistical analysis was performed to analyze differences between the 2 groups. Results: There was no significant difference between the groups with regard to age at ACLR, sex distribution, time from injury to surgery ( P > .05), proportion of professional athletes, presence of femoral bone bruise, or technical aspects of surgery. The overall extension deficit incidence was significantly higher in the Cyclops group at 3 weeks (Cyclops, 71%; control, 22%) ( P < .001) and at 6 weeks (Cyclops, 60%; control, 7%) ( P < .001). The extension deficit related to hamstring contracture was significantly higher in the Cyclops group at 3 weeks (Cyclops, 58%; control, 22%) ( P < .001) and at 6 weeks (Cyclops, 29%; control, 2%) ( P < .001). Conclusion: The Cyclops lesion is associated with a persistent hamstring contracture at 3 and 6 weeks after ACLR.